Tren Penelitian Pembelajaran Maharah Kalam berbasis Media Digital di Indonesia: Systematic Literature Review - Shiha Zavirma Hero; Khizanatul Hikmah (Universitas Muhammadiyah Gorontalo, 2025)
In the 21st century, Arabic language learning is accessible at any time and from any location. Maharah Kalam is a skill that students are required to master in order to engage in active Arabic discourse. The advent of new technologies has facilitated students' learning through a plethora of multimedia resources, including digital learning materials. The advent of numerous digital media has, on occasion, given rise to a new challenge: determining which digital media is most suitable for the specific needs of each student. The objective of this literature review is to identify the various digital media employed in the teaching of maharah kalam in Indonesia. This study employs the method of systematic literature review (SLR), with the objective of identifying the various digital media utilized in the teaching of maharah kalam in Indonesia. To this end, 15 scientific articles published within the past five years, spanning the period from 2019 to 2024, have been selected as the subject of this study. The findings of the study indicate that the most frequently utilized digital media is the vlog. Seven digital media have been identified as having a significant impact on the advancement of Arabic language learning in Indonesia, namely vlog, YouTube, Duolingo, Website learning.aljazeera.net, Alef Education media, WhatsApp, and Plotagon.